Genesis and emplacement of felsic Variscan plutons within a deep crustal lineation, the Penacova-Regua-Verin fault: An integrated geophysics and geochemical study (NW Iberian Peninsula) - H. C. B. Martins (2009)
Multidisciplinary studies integrating, U-Pb geochronology, whole-rock geochemical data, isotope geochemistry, anisotropy of magnetic susceptibility (AMS) studies and gravimetry were carried out on the Vila Pouca de Aguiar and the Aguas Frias-Chaves porphyritic biotite granite plutons. Both plutons occur independently in a distance of about 20 km. The Vila Pouca de Aguiar and Aguas Frias-Chaves plutons are examples of late to post-orogenic felsic Variscan granites in northern Portugal (NW Iberian Peninsula). The U-Pb zircon analyses yield a consistent age of 299 +/- 3 Ma which is considered to be the emplacement age of the two plutons. These granites are weakly peraluminous, show high HREE and Y (and low P) contents which are consistent with them being I-type. This is also supported by their weakly evolved isotopic compositions, (87)Sr/(86)Sr(i) = 0.7044-0.7077 and epsilon Nd = - 2.0 to - 2.6, as well as by the whole rock oxygen isotope (delta(18)O VSMOW) ranging from + 9.7 parts per thousand to + 11.0 parts per thousand. The emplacement of granite magma took place after the third Variscan deformation phase (D(3)) in an extensional tectonic regime, large scale uplift and crustal thinning. The integration of different data suggests that both plutons have the same feeding zone aligned within the Penacova-Regua-Verin fault (PRVF) and that both have the same structure which is related to late Variscan phases. The thicker shape for the Aguas Frias-Chaves pluton comparing to that of the Vila Pouca de Aguiar pluton is compatible with different depths of PRVF sectors. The available data led us to propose a model of partial melting of a meta-igneous lower crustal source rather than an open-system of mantle-crust interaction. The interaction between the continental crust and invading malfic magmas could have been limited to mere heat transfer and, perhaps, local intermingling.